Cornified Epithelial Teeth of Jawless Vertebrates Contain Proteins Similar to Keratin-Associated Proteins of Mammalian Skin Appendages - Attila Placido Sachslehner; David A. D. Parry; Leopold Eckhart (Journal of Developmental Biology)
Keratins and keratin-associated proteins (KRTAPs) are the main components of mammalian nails and hair. Comparative genomics and gene expression studies have revealed that keratins are conserved in all vertebrates, whereas KRTAPs exist only in mammals. Recently, we found hair keratin-like cysteine-rich keratins in jawless vertebrates with confirmed expression in the cornified epithelial teeth of the sea lamprey (Petromyzon marinus). Here, we report that KRTAP-like proteins are also present in the horny teeth of the lamprey. Mass spectrometry-based proteomics identified proteins that share features with KRTAPs, such as high contents of cysteine and tyrosine residues, which support intermolecular interactions, and abundant glycine residues, which endow the proteins with flexibility. Genes encoding KRTAP-like proteins are arranged in a cluster in P. marinus, and the presence of at least one KRTAP-like protein is conserved in phylogenetically diverse species of lamprey, including Lampetra fluviatilis, Lethenteron reissneri, Geotria australis, and Mordacia mordax. The KRTAP-like genes of lampreys contain two exons, whereas mammalian KRTAPs have only a single exon. Although KRTAPs and KRTAP-like proteins are products of independent evolution, their common expression in cornified skin appendages suggests that they fulfill similar functions.